How to make patent drawings : a patent it yourself companion - Lo, Jack (Nolo, 2011)
"Explains preparing formal patent drawings that comply with the rules of the U.S. Patent and Trademark Office. The 6th edition contains the latest forms, plus new patent rules for application and prosecution"--